Effect of low-intensity versus high-intensity resistance training on the functioning of the institutionalized frail elderly. Issue 3 (September 2018) - Sahin, Ulku K.; Kirdi, Nuray; Bozoglu, Ergun; Meric, Aydin; Buyukturan, Galip; Ozturk, Ahmet; Doruk, Huseyin
Abstract : Frailty has emerged as an important risk factor for disability. Age-related declines in physical and physiological function lead to increased risk of loss of independence and poor quality of life. Recent evidence has shown the effectiveness of physical exercise programmes in preventing or reversing frailty. The aim of this study was to evaluate changes in the functioning of frail elderly individuals after undergoing resistance training for 3 days a week for 8 weeks. The effectiveness of exercise training was investigated in 48 frail elderly individuals who were randomly assigned to the following intervention groups: high-intensity (HI; n =16; age: 69–96 years) or low-intensity (LI; n =16; age: 77–93 years) strength training groups or a control group ( n =16; age: 76–93 years) with no specific exercise programme. Participants were assessed for muscle strength, physical function, activities of daily living, depression and quality of life. The HI group had significantly better results ( P <0.05) on the Short Physical Performance Test than the LI group; however, the LI group did show a significant improvement in those scores, whereas the scores of the control group worsened. Results for the other evaluations were similarly favourable in both exercise groups ( P >0.05). The study showed that LI exercise was as effective as HI exercise for most parameters tested. Exercise training is useful for the prevention or treatment of frailty, as it improves functioning by contributing positively to muscle strength, gait, balance and quality of life.